Educação Bilíngue e Cultura Surda: interlocuções à Identidade Bicultural - (:unkn) unknown (Universidade Estadual de Goiás, 2022)
This research presents Bilingual-Bicultural Education in the context of deafness as its theme. The problem question that gave rise to the investigation was: to what extent can Bilingual Education provide inclusive development to the deaf community by boosting identity and cultural development? The general objective of the research is: to analyze narratives of deaf people to identify if there is relevance in Bilingual Education in cultural and identity development and in overcoming communication barriers. From the methodological point of view, the study is configured in a research with a qualitative, phenomenological, bibliographical and empirical approach, being developed theoretical exploration and narrative research proposal with the participation of 03 (three) deaf people over 18 (eighteen) years old. The focus of the research was anchored on the issue of cultural and identity formation of the participants in relation to the life history of these people, to Sign Language and its contributions. Therefore, the study is based on authors and legal documents that develop studies on culture, Deaf Culture, education, inclusion, Deaf Identity and Bilingual Education. Mello (2009), Geertz (2008), Eagleton (2011), Certeau (1995), Laraia (2001) and Bauman (2012) supported the discussion on the concept of culture. Bagno (2013), Quadros (1997; 2015), Saussure (2006), Laborit (2000), Vilhalva (2004), Brasil (1996; 2002; 2005; 2021) were fundamental to reflect on language, Bilingualism and Bilingual Education. Stuart Hall (1997; 2006) and Skliar (1998; 2005) based their research on the relationship between education and identities, with Strobel (2008), Campos and Stumpf (2012), Sá (2010), Perlin (2005), Gesser ( 2009), Dammeyer and Marschark (2016) helped in this reflection on the cultural and identity specificity in the context of deafness. For that, Clandinin and Connelly (2015), Muylaert, Júnior, Gallo, Neto, Reis (2014) and Minayo (2014; 2009) anchored in the developed methodological processes. The results obtained from theoretical and empirical linkage and their links indicated the emergence of eight units of meaning, namely: i) Libras, language as identity; ii) social acceptance of deafness; iii) isolation, loneliness; iv) social interest; v) accessibility; vi) Bilingual Education and bilingual society; vii) inclusion and Inclusive Education; viii) Deaf Culture and the Bicultural. The results led us to understand and conclude culture as a social construction of meanings, part and participant of the subject's social and identity constitution, as an expression of the essence of the human being, of its differentiations and specificities, of its political character, as identity, passed through and transformed by communication systems. The fact was pointed out that education in the context of deafness still needs long-term investments that ratify what it is to be deaf, that anchors its existence based on phenomena and experiences of the deaf person. It was possible to reveal, then, that the acquisition and development of language and its manifestations in language through Sign Language launches the possibility of understanding the world for the deaf person and re-signifies their existence in it, that is, it represents the possibility of cultural and identity development. Therefore, the “bi” in the context of deaf education needs to be shifted from meaning “between” to “beyond”.
Bilingual Education and Deaf Culture : interlocutions to Bicultural Identity
Keywords: Educação Bilíngue.; Bicultural; Cultura Surda; Identidades Surdas; Bilingual Education; Bicultural; Deaf Culture; Deaf Identities; CIENCIAS HUMANAS::EDUCACAO